2017
DOI: 10.1073/pnas.1711158114
|View full text |Cite
|
Sign up to set email alerts
|

Role of remodeling and spacing factor 1 in histone H2A ubiquitination-mediated gene silencing

Abstract: Posttranslational histone modifications play important roles in regulating chromatin-based nuclear processes. Histone H2AK119 ubiquitination (H2Aub) is a prevalent modification and has been primarily linked to gene silencing. However, the underlying mechanism remains largely obscure. Here we report the identification of RSF1 (remodeling and spacing factor 1), a subunit of the RSF complex, as a H2Aub binding protein, which mediates the gene-silencing function of this histone modification. RSF1 associates specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 71 publications
(81 reference statements)
5
53
0
Order By: Relevance
“…Moving forward, an important challenge remains to examine in detail the molecular mechanisms by which H2AK119ub1 could contribute to gene repression. This may involve reader proteins that recognize H2AK119ub1 (Cooper et al., 2016, Kalb et al., 2014, Richly et al., 2010, Zhang et al., 2017), or H2AK119ub1 may directly counteract transcription, as suggested by recent observations using in vitro assays (Aihara et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, an important challenge remains to examine in detail the molecular mechanisms by which H2AK119ub1 could contribute to gene repression. This may involve reader proteins that recognize H2AK119ub1 (Cooper et al., 2016, Kalb et al., 2014, Richly et al., 2010, Zhang et al., 2017), or H2AK119ub1 may directly counteract transcription, as suggested by recent observations using in vitro assays (Aihara et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that H2AK119ub1 directly disrupts RNA Pol II activity (Stock et al, 2007;Zhou et al, 2008), as suggested by in vitro transcription assays (Aihara et al, 2016;Nakagawa et al, 2008). Alternatively, H2AK119ub1 could recruit reader proteins that elicit gene repression (Ali et al, 2018;Cooper et al, 2016;Qin et al, 2015;Richly et al, 2010;Zhang et al, 2017) or interfere with deposition of histone modifications that facilitate transcription (Nakagawa et al, 2008;Yuan et al, 2013). Finally, it is possible that PRC1 drives gene repression via ubiquitylation of histone H2A variants (Surface et al, 2016) or other non-histone substrates (Ben-Saadon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above, USP22 regulates the abundance of H2Aub1 and H2Bub1 to promote gene expression and is therefore considered a transcriptional activator. H2Aub1, which is catalyzed by the Polycomb Repressive Complex 1 (PRC1), is enriched within the promoter regions of polycomb target genes, promotes the recruitment of PRC2 repressive complex and promotes transcriptional repression [ 25 , 59 , 60 ]. Therefore, USP22 is proposed to promote transcription of polycomb targets by reversing H2A ubiquitination [ 9 ].…”
Section: Usp22 Is a Transcriptional Activatormentioning
confidence: 99%